2017
DOI: 10.1007/s10461-017-1969-1
|View full text |Cite
|
Sign up to set email alerts
|

Preference of Oral Tenofovir Disoproxil Fumarate/Emtricitabine Versus Rectal Tenofovir Reduced-Glycerin 1% Gel Regimens for HIV Prevention Among Cisgender Men and Transgender Women Who Engage in Receptive Anal Intercourse with Men

Abstract: Oral pre-exposure prophylaxis (PrEP) can prevent HIV transmission. Yet, some may prefer not to take systemic daily medication. MTN-017 was a 3-period, phase 2 safety and acceptability study of microbicide gel applied rectally either daily or before and after receptive anal intercourse (RAI), compared to daily oral tablet. At baseline, cisgender men and transgender women who reported RAI (N=187) rated the daily oral regimen higher in overall liking, ease of use, and likelihood of future use than the gel regimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…Few demographic variables were predictive of product use trajectories, with the exception of age (for both regimens) and being TW (for the oral tablet). Findings on acceptability and likelihood of use from this study (Carballo-Diéguez et al, 2017) and from another on oral PrEP (Sineath et al, 2013) also demonstrated no association with demographic variables. Two studies of vaginal microbicide gel use demonstrated lower adherence among a younger age group.…”
Section: Discussioncontrasting
confidence: 75%
“…Few demographic variables were predictive of product use trajectories, with the exception of age (for both regimens) and being TW (for the oral tablet). Findings on acceptability and likelihood of use from this study (Carballo-Diéguez et al, 2017) and from another on oral PrEP (Sineath et al, 2013) also demonstrated no association with demographic variables. Two studies of vaginal microbicide gel use demonstrated lower adherence among a younger age group.…”
Section: Discussioncontrasting
confidence: 75%
“…In an extended safety and acceptability study of the RGVF gel applied rectally, MTN‐017, side effects remained very low, adherence very high, and on‐demand dosing of the gel was preferred to daily gel dosing . Participants were not so enamored of the rectal gel applicator, borrowed from the vaginal development program, and consensus among investigators was that applicator dosing would not be acceptable in extended RCTs . MTN‐014 demonstrated poor penetration of TFV into vaginal tissue after rectal RGVF dosing, indicating a future TFV rectal product applied rectally would not likely perform well protecting vaginal HIV infection …”
Section: Last and Next Generation Tfv Microbicide Developmentmentioning
confidence: 99%
“…Rectal microbicides are in demand as alternatives to oral PrEP due to the very high risk of unprotected RAI in MSM and TGW as well as significant minorities of MSM and TGW (27% in MTN-017) indicating oral daily TDF/FTC as their least preferred regimen (compared to on-demand and daily gel regimens); these participants also indicated displeasure with the rectal gel applicator in the gel arms of the study. 100 Important numbers of MSM and TGW struggle to maintain adherence on PrEP as, for example, most of PrEP demonstration project failures are in persons without detectable ARVs in their blood. MSM and TGW advocates and community level discussions have long indicated a high level of interest for on-demand, behaviorally congruent PrEP with lubricants or anal douches.…”
Section: Rectal Microbicide Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) For example, during MTN 017, a study in which participants had the chance to compare daily oral PrEP and a topical PrEP rectal gel candidate, 28% of participants reported that daily oral PrEP was their least favorite prevention strategy and that they were more likely to use a topical microbicide gel in the future if it were effective against HIV. (6) Another study in Peru also found that, among transgender women and men who have sex with men, 57% of participants would prefer a topical PrEP rectal gel compared to 29% who preferred oral PrEP. (7) Furthermore, although efforts are underway in the HIV prevention research field to develop a vaccine, as with oral PrEP, uptake among those at risk for HIV will likely depend on individual preferences and concerns about factors including vaccine efficacy, duration of protection, cost, and safety.…”
Section: Introductionmentioning
confidence: 99%